2015
DOI: 10.1093/ejcts/ezv375
|View full text |Cite
|
Sign up to set email alerts
|

Has the quality of reporting of randomized controlled trials in thoracic surgery improved?

Abstract: Our study suggests that the quality of reporting in the thoracic surgery literature is improving with time and is predicted by factors including number of authors, multicentre trials, type of comparison, time period of publication and industry sponsorship. Ongoing efforts should be made to improve the quality of reporting in thoracic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Many journals already require submission of a CONSORT checklist and participant flow diagram, which may explain improvements in RCT reporting generally when assessed against CONSORT 2010 [6,7,5], lending further credibility to our argument that greater journal endorsement of CONSORT-PRO will improve the standard of PRO reporting. The fact that we obtained controls (i.e.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Many journals already require submission of a CONSORT checklist and participant flow diagram, which may explain improvements in RCT reporting generally when assessed against CONSORT 2010 [6,7,5], lending further credibility to our argument that greater journal endorsement of CONSORT-PRO will improve the standard of PRO reporting. The fact that we obtained controls (i.e.…”
Section: Discussionmentioning
confidence: 52%
“…The CONSORT Statement has been endorsed by over 600 medical journals, by major editorial organisations and has been cited in over 8000 publications [4]. Trials published in journals that endorse the CONSORT Statement are reported more completely than those in non-endorsing journals [5]; and improved reporting of RCTs over time in thoracic surgery [6] and traumatic brain injury [7] has been attributed to the use of the CONSORT statement.…”
Section: Preliminary Evidence On the Uptake Use And Benefits Of The mentioning
confidence: 99%
“…The score was at an intermediate level compared with those of RCTs in other surgical areas, such as pediatric, thoracic, urological, otolaryngological, and cardiothoracic surgery, in which the proportions of reported CONSORT items ranged from 50.5% to 72.3%. [22][23][24][25][26] The adherence of the RCTs of bariatric surgery to the NPT extension, regrettably, was poor. A median score of 26.8…”
Section: Discussionmentioning
confidence: 99%